On the Coefficients of Several Classes of Bi-Univalent Functions Defined by Convolution (Communications in Mathematical Research, 2020)
In this paper, we introduce several new subclasses of the function class$\itΣ$ of bi-univalent functions analytic in the open unit disc defined by convolution.Furthermore, we investigate the bounds of the coefficients $|a_2|$ and $|a_3|$ for functionsin these new subclasses. The results presented in this paper improve or generalizethe recent works of other authors.
Keywords: analytic and univalent functions; coefficient; bi-univalent function; Hadamard product; convolution